2015
DOI: 10.1007/s12257-014-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of chitin and chitosan with antimicrobial and antioxidant activities from cosmopolitan Orthoptera species (Insecta)

Abstract: This study examined two gregarious Orthoptera species (Calliptamus barbarus and Oedaleus decorus) as potential sources of chitin. The chitin content of the dry weight of C. barbarus was 20.5 ± 0.7%, and it was 16.5 ± 0.7% for O. decorus. Furthermore, the yield of chitosan (70 75% deacetylation degree) from the grasshopper species was found to be 74 ~ 76%, which is close to the yield of commercial preparations obtained from the unused parts of crabs and shrimp. The chitin and chitosan obtained in this way were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
94
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 56 publications
19
94
2
Order By: Relevance
“…No et al (2003), reported a reduction of up to 7.5 logarithmic cycles of V. parahaemolyticus in 24 h at 37 • C, using the same chitosan concentration than in our study, but with a lower molecular weight (81 KDa). Similar inhibition concentrations were reported by Yang et al (2005) who was able to reduce 7 log cycles of E. coli in 6 h at 37 • C. Kaya et al (2015) presented similar inhibition of V. alginolyticus with chitosan obtained from insects (cosmopolitan Orthoptera species); the effect was even better than the antibacterial activity presented by standard antibiotics. Raafat and Sahl (2009) explains that a MW higher than 100 KDa is required for chitosan to present microbial inhibition.…”
Section: Conditionsupporting
confidence: 83%
“…No et al (2003), reported a reduction of up to 7.5 logarithmic cycles of V. parahaemolyticus in 24 h at 37 • C, using the same chitosan concentration than in our study, but with a lower molecular weight (81 KDa). Similar inhibition concentrations were reported by Yang et al (2005) who was able to reduce 7 log cycles of E. coli in 6 h at 37 • C. Kaya et al (2015) presented similar inhibition of V. alginolyticus with chitosan obtained from insects (cosmopolitan Orthoptera species); the effect was even better than the antibacterial activity presented by standard antibiotics. Raafat and Sahl (2009) explains that a MW higher than 100 KDa is required for chitosan to present microbial inhibition.…”
Section: Conditionsupporting
confidence: 83%
“…Chitin is one of the most abundant amino polysaccharides found Q3 in nature next to cellulose; it has a wide variety of sources as exoskeleton of crustacean (crab, shrimp and crawfish, Oniscus asellus) [1][2][3][4], insect cuticles (Melolontha melolontha) [3], Orthoptera species [5,6], wings of cockroach [7], grasshopper species [8], medicinal fungus [9], larvae and adult Colorado potato beetle [10], aquatic invertebrates [11], bat guano [12], resting eggs of Daphnia longispina [13], spider species [14], Daphnia magna resting eggs [15], and cell wall of fungi and in the green algae. The chemical structure of chitin (C 8 H 13 O 5 N) n is similar to cellulose, having one hydroxyl group on each monomer substituted with an acetyl amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…CHI is biocompatible, biodegradable and has interesting properties (e.g., antimicrobial and antioxidant activities) that justify its use in multiple fields such as biology, food nutrition, medicine (e.g., tissue engineering), and pharmacy [38][39][40][41][42]. CHI based tissues should mimic the behavior of the replaced tissue, being an ideal system with a practically insoluble outer surface and an inner surface (i.e., in contact with the tissue) capable to experience a progressive degradation and a complete resorption after finishing the regeneration process.…”
Section: Bionanocompositesmentioning
confidence: 99%